2007
DOI: 10.15288/jsad.2007.68.879
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum and Alcohol-Related Factors Associated With the Relapse of Risky Drinking

Abstract: Objective-The purposes of this investigation were (1) to describe postpartum drinking patterns among women who were frequent drinkers before pregnancy and (2) to identify factors correlated with postpartum "risky" drinking among women who were frequent drinkers before pregnancy.Method-Information was gathered through a self-administered questionnaire completed at the postpartum visit and a subsequent face-to-face interview of 381 women, recruited from 35 obstetric/ gynecologic clinics throughout Wisconsin, who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
29
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 18 publications
3
29
3
Order By: Relevance
“…The majority of research has focused on smoking relapse postpartum (Colman and Joyce, 2003;Gyllstrom et al, 2012;Kaneko et al, 2008;Park et al, 2009;Ruger et al, 2008;Tong et al, 2008;Tran et al, 2013;Yasuda et al, 2013), with only a handful of studies looking at postpartum alcohol relapse (Ebrahim et al, 1998;Fleming, 2007a, 2007b;Nayak and Kaskutas, 2004). One of these studies found that at six to 12 weeks postpartum 37.8% of women who were frequent drinkers before pregnancy reported postpartum risky drinking, with 18% reporting heavy episodic drinking, 5% frequent drinking only and 15% reporting both behaviors (Jagodzinski and Fleming, 2007a). Another study found that women who reported at risk drinking postpartum were almost six times more likely to have had at risk drinking prior to pregnancy (Jagodzinski and Fleming, 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…The majority of research has focused on smoking relapse postpartum (Colman and Joyce, 2003;Gyllstrom et al, 2012;Kaneko et al, 2008;Park et al, 2009;Ruger et al, 2008;Tong et al, 2008;Tran et al, 2013;Yasuda et al, 2013), with only a handful of studies looking at postpartum alcohol relapse (Ebrahim et al, 1998;Fleming, 2007a, 2007b;Nayak and Kaskutas, 2004). One of these studies found that at six to 12 weeks postpartum 37.8% of women who were frequent drinkers before pregnancy reported postpartum risky drinking, with 18% reporting heavy episodic drinking, 5% frequent drinking only and 15% reporting both behaviors (Jagodzinski and Fleming, 2007a). Another study found that women who reported at risk drinking postpartum were almost six times more likely to have had at risk drinking prior to pregnancy (Jagodzinski and Fleming, 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…Prevalence estimates of “any alcohol use” postpartum range from 30% to nearly 50%, and binge drinking range from 6% to nearly 20% (Jagodzinski & Fleming, 2007b; Laborde & Mair, 2012; Muhuri & Gfroerer, 2009). In addition to the well-established harmful effects of risky drinking (defined by the National Institute of Alcohol Abuse and Alcoholism as consuming more than 3 drinks per occation or more than 7 per week for women) on mothers’ own health (Fan et al, 2008), two pathways have been suggested hypothesizing how mother’s alcohol use can pose a significant risk to the child’s well-being.…”
mentioning
confidence: 99%
“…This indicates that maternal postpartum drinking patterns may be characterized by intra-individual differences in inter-individual change. However, to date, most empirical studies have measured maternal postpartum drinking information at a single point-in-time, usually short of one year post-delivery follow-up (Jagodzinski & Fleming, 2007b; Laborde & Mair, 2012; McLeod, Pullon, Cookson, & Cornford, 2002), with some exceptions (Bailey, Hill, Hawkins, Catalano, & Abbott, 2008; Wolfe, 2009). To our knowledge, no study has assessed maternal drinking over the potentially stressful period of parenting until children enter kindergarten.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Alarmingly, the prevalence of binge drinking (which is the most harmful pattern of consumption) during pregnancy has been reported to be: 7.4% in Russia (Kristijanson, Wilsnack, Zvartau, Tsoy, & Novikov, 2007), 8.3% in the United States (Ethen et al, 2009), and 9.5% in Sweden (Magnusson, Göransson, & Heilig, 2005). Moreover, the prevalence of alcohol consumption and binge drinking has been reported to be much higher among high-risk women (Jagodzinski & Fleming, 2007;Kelly et al, 2011;Muckle et al, 2011).…”
Section: Introductionmentioning
confidence: 99%